Going Up or Going Mad? - Papadima, Aspasia (My University, 2023)
Excerpt from "The 5th Emirates International Poster Festival: Design for Climate Change, Dubai" Call: "[...]In the face of escalating climate impacts, from extreme weather events to biodiversity loss, designers from around the world are invited to harnesses their creative prowess to tackle this pressing crisis head-on. Through captivating visuals and compelling concepts, EIPF serves as a powerful platform to inspire positive action and mobilize individuals, communities, and policymakers towards a shared mission: safeguarding our planet for future generations. These posters not only focus on aesthetics but also effectively convey the importance of addressing climate change and its impact on our environment and society. Through visual representations of the consequences of global warming and environmental degradation, these designs compel viewers to confront the realities of our changing world.[...]"